2012
DOI: 10.1186/1471-2377-12-71
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in Parkinson’s disease: a community-based study in Norway

Abstract: BackgroundThe purpose of this study was to examine the prevalence of sleep problems in a community-based sample of patients with Parkinson’s disease (PD) in Norway, and their associated factors.Methods176 consecutive PD outpatients (41% females) were included in a study of non-motor symptoms, including sleep problems. All participants responded to the Parkinson’s Disease Sleep Scale (PDSS), where an overall score below 82 or a score below 5 on a sub-item indicate possible sleep problem. Factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…We found that the poor sleepers had significant higher UPDRS scores. Our finding contrasted with a community‐based study in Norway (Svensson et al., 2012), but is in agreement with a case–control study conducted in India (Kumar et al., 2002). In addition, poor sleep was positively correlated with the dosage of levodopa and hypnotics in our and two other studies (Antczak et al., 2013; Verbaan, van Rooden, Visser, Marinus, & van Hilten, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the poor sleepers had significant higher UPDRS scores. Our finding contrasted with a community‐based study in Norway (Svensson et al., 2012), but is in agreement with a case–control study conducted in India (Kumar et al., 2002). In addition, poor sleep was positively correlated with the dosage of levodopa and hypnotics in our and two other studies (Antczak et al., 2013; Verbaan, van Rooden, Visser, Marinus, & van Hilten, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Some authors have argued that EDS could be an integral part of PD rather than the result of poor nighttime sleep quality (Goldman et al., 2013). In addition, whether clinical characteristics such as disease severity, Unified Parkinson's Disease Rating Scale (UPDRS) score, and the prescription of dopaminergic medication are risk factors for sleep disturbance remains controversial (Hoglund, Broman, Palhagen, Fredrikson, & Hagell, 2015; Kumar, Bhatia, & Behari, 2002; Ondo et al., 2001; Pandey, Bajaj, Wadhwa, & Anand, 2016; Svensson, Beiske, Loge, Beiske, & Sivertsen, 2012; Tholfsen, Larsen, Schulz, Tysnes, & Gjerstad, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Some specific sleep scales for PD populations find more sleep complaints in PD patients with RLS than in PD patients without RLS. The relationship between Parkinson's Disease Sleep Scale (PDSS) and RLS remained still significant when item on nocturnal restlessness was removed from the analysis [10]. In the current study, there appeared more daytime sleepiness (SEDS >15), other sleep complaints and low quality of life (WHO5 <50: 39.9 vs. 54.3%, adjusted OR 1.58, 95% CI 1.03-2.44) in the PD-RLS group.…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor symptoms, including sleep disorders, for example, RLS, are important features of the disease. The prevalence of RLS in PD cohorts has varied from 5.5 to 27% in European studies [7,8,9,10,11]. The prevalence of RLS in drug-naïve patients with PD has varied from 5.5 to 16.5% [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies on PD patients have reported the prevalence of insomnia symptoms [6,7] or insomnia according to one compound question [8,9] or subthreshold insomnia [10]. Lastly insomnia is known to overlap with multiple medical problems and comorbid sleep disorders.…”
Section: Introductionmentioning
confidence: 98%